2013
DOI: 10.1246/bcsj.20130131
|View full text |Cite
|
Sign up to set email alerts
|

trans-Bisglycoconjugation is an Efficient and Robust Architecture for PDT Photosensitizers Based on 5,10,15,20-Tetrakis(pentafluorophenyl)porphyrin Derivatives

Abstract: To examine the versatility of the trans-bisglycoconjugation architecture for 5,10,15,20-tetrakis(pentafluorophenyl)porphyrin (TFPP) derivative-based photodynamic therapy (PDT), 25 porphyrin derivatives bearing d-glucopyranose moieties were prepared, and their in vitro photocytotoxicities were examined. trans-Bisglycoconjugated TFPP derivatives exerted the best photocytotoxicity among TFPP derivatives in the same category, regardless of the central metal ion and the type of glycoconjugation. trans-Bisglycoconju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The EC 50 value of 7 was 1−5 nM which was almost the same as that of 3 (1−5 nM) and lower than that of 8 (50−100 nM). Similar to the photocytotoxicities of a series of glycosylated porphyrins, 28,30 transbisthioglycosylated chlorin 7 exerted greater photocytotoxicity than that of fully glycosylated chlorin 8. The superiority of 7 compared with 3 was significant at wavelengths >600 nm (Figure 2b).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 78%
See 1 more Smart Citation
“…The EC 50 value of 7 was 1−5 nM which was almost the same as that of 3 (1−5 nM) and lower than that of 8 (50−100 nM). Similar to the photocytotoxicities of a series of glycosylated porphyrins, 28,30 transbisthioglycosylated chlorin 7 exerted greater photocytotoxicity than that of fully glycosylated chlorin 8. The superiority of 7 compared with 3 was significant at wavelengths >600 nm (Figure 2b).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 78%
“…The enhanced uptake of trans-bisthioglycosylated chlorin 7 compared with that of fully glycosylated chlorin 8 is similar to that of the glycosylated porphyrin series. 28,30 Therefore, cellular uptake was controlled solely by the peripheral glycosylation pattern and not by the core structure. In contrast, the absorption of light was mainly due to the core structure.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…Owing to their polar substituents (OH and NH) and the hydrophobic porphyrin skeleton, these compounds exhibit a ‘medium’ polarity, which is also found in clinically applied photosensitizers, such as Temoporfin or TOOKAD . Moreover, trans ‐A 2 B 2 ‐porphyrins that carry polar substituents have been reported to exhibit a high PDT activity . Hence, compounds 12e , 12h , 12i , and the bisamino‐substituted precursor 11b were selected for testing against four tumor cell lines: human epidermoid carcinoma cell lines A431 and A253, squamous carcinoma cell line CAL‐27, and colorectal adenocarcinoma cell line HT29 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…[50] Moreover, trans-A 2 B 2 -porphyins carrying polar substituents have been reported to exhibit a high PDT activity. [51] Hence, compounds 12e, 12h, 12i and the bisamino-substituted precursor 11b were selected for testing against four tumor cell lines (Figure 5a-d): Human epidermoid carcinoma cell lines A431 and A253, respectively, squamous carcinoma cell line CAL-27, and colorectal adenocarcinoma cell line HT29. In brief, cells were incubated for 24 h with a solution of either 0, 2 or 10 µmol/L concentration of the photosensitizer and medium, then the medium was changed (to assure that only photosensitizer taken up by the cells contributes to the effect) and the cells were irradiated with light of 652 nm (corresponding to the longest wavelength absorption band of the porphyrins); after another incubation period (24 h) with medium the vitality of the cells was determined using the XTT-test (see experimental section for details).…”
Section: Cell Testingmentioning
confidence: 99%
“…The malignant cells are known to overexpress carbohydrate-binding proteins. The porphyrin-based molecules can be targeted toward cell surface receptors particularly known as carbohydrate-binding lectins, by linking hexose sugars/oligosaccharides on the molecules. Glycoconjugated porphyrinoids have been nicely summarized in the recent review by Drain and co-workers, such molecules have shown good solubility and higher cellular uptake due to enhanced interactions with tumor cell receptors . Thus, carbohydrate–porphyrin conjugates are promising candidates for PDT; attachment of sugars make them amphiphilic in nature and helps in their cellular uptake in tumor cells. However, the ongoing research on novel glycoporphyrin conjugates for PDT is challenging, due to the lack of straightforward synthetic protocols to prepare such molecules in large quantities. The well-established methods of porphyrin syntheses reported by Lindsey and co-workers and Alder and co-workers are not favorable to prepare glycosylated porphyrins in good yields. , The available glycoconjugates of porphyrins were synthesized either by condensation of pyrrole with carbohydrate-linked benzaldehydes , or by using click chemistry to link hexose sugars to the functionalized porphyrin through triazole units. , Tetrasubstituted O -linked and S -linked glycoporphyrin conjugates were prepared by substituting the para -position of the meso -aryl groups of porphyrins; this method is mostly used to make A 4 type carbohydrate–porphyrins conjugates. , Glycosylated porphyrins have exquisite photophysical properties, and literature supports the hypothesis of improved cellular uptake and photocytotoxicity for glycosylated porphyrins as compared to nonfunctionalized systems. , The biological behavior of the reported glycosylated porphyrins differs depending upon the number of monosaccharide units attached at the meso -positions, which affect the cellular uptake and photocytotoxicity toward cancer cells .…”
Section: Introductionmentioning
confidence: 99%